Photoacoustic signal enhancement in dual-contrast gastrin-releasing peptide receptor-targeted nanobubbles - Zhao, Shensheng; Lee, Leanne; Zhao, Yang; Liang, Nu-Chu; Chen, Yun-Sheng (Frontiers in Bioengineering and Biotechnology, 2023)
Translatable imaging agents are a crucial element of successful molecular imaging. Photoacoustic molecular imaging relies on optical absorbing materials to generate a sufficient signal. However, few materials approved for human use can generate adequate photoacoustic responses. Here we report a new nanoengineering approach to further improve photoacoustic response from biocompatible materials. Our study shows that when optical absorbers are incorporated into the shell of a gaseous nanobubble, their photoacoustic signal can be significantly enhanced compared to the original form. As an example, we constructed nanobubbles using biocompatible indocyanine green (ICG) and biodegradable poly(lactic-co-glycolic acid) (PLGA). We demonstrated that these ICG nanobubbles generate a strong ultrasound signal and almost four-fold photoacoustic signal compared to the same concentration of ICG solution; our theoretical calculations corroborate this effect and elucidate the origin of the photoacoustic enhancement. To demonstrate their molecular imaging performance, we conjugated gastrin-releasing peptide receptor (GRPR) targeting ligands with the ICG nanobubbles. Our dual photoacoustic/ultrasound molecular imaging shows a more than three-fold enhancement in targeting specificity of the GRPR-targeted ICG nanobubbles, compared to untargeted nanobubbles or prostate cancer cells not expressing GRPR, in a prostate cancer xenograft mouse model in vivo.